2021
DOI: 10.22161/jhed.3.3.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Resources Management Skills on Accounting Information Quality in Kurdistan Public Sector

Abstract: The article's purpose is to measure the impact of human resources management skills on accounting information quality in kurdistan public sector. To enable the study to measure human resource management skills at public sectors in Kurdistan region of Iraq, the researchers used five human resources management skills elements, first is communication skill, second is flexibility skill, third is negotiation skill, fourth is ethical action skill, and fifth is compassion skill. To assess the current study, the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…If users understand and use the system, success will follow. This also agrees with the research of Qader et al, (2021), who found that an increase in HR competence was reflected by an incerease in accounting information systems, and vice versa.…”
Section: Competence Of Human Resources (Hr)supporting
confidence: 92%
“…If users understand and use the system, success will follow. This also agrees with the research of Qader et al, (2021), who found that an increase in HR competence was reflected by an incerease in accounting information systems, and vice versa.…”
Section: Competence Of Human Resources (Hr)supporting
confidence: 92%
“…Competence is a crucial outcome inside an organization since it plays a significant role in facilitating operational efficiency and the attainment of organizational objectives. Qader et al, (2021) posits that Human Resource Competence can be regarded as a scientific discipline that delineates the methodologies for effectively and practically executing job tasks. According to Moraes et al, (2019), the indicators of Human Resource Competence encompass various factors, namely: (1) Motive, (2) Trait (Personal Characteristics), ( 3) Attitude (Self-Concept), (4) Knowledge, (5) Skill, and (6) Management Participation.…”
Section: The Proficiency Of Human Resourcesmentioning
confidence: 99%
“…The eligibility of the government apparatus is a Interdisciplinary Social Studies, 2(10), Jul 2023 factor that determines whether a region can/is able to carry out its household affairs properly or not (Nahar et al, 2018). However, the success or failure of an activity, in this case the implementation of regional autonomy, will depend heavily on the human actors or the competence of Human Resources (HR) from the Government regulations themselves (Enders et al, 2013;Qader et al, 2021). If the performance is still not in accordance with the talents, interests and abilities, or not in accordance with the qualifications available, it can be said that the competence of Human Resources has not shown good performance (Jumady & Lilla, 2021;Meswantri & Awaludin, 2018).…”
Section: Introductionmentioning
confidence: 99%